Design and Implementation of Intelligent Learning System Based on Big Data and Artificial Intelligence - Yang, Yawen (Frontiers in Psychology, 2021)
In order to improve the level of education development in remote areas of China, help minority schools to better play the advantages of multimedia network teaching resources provided by the state, and further improve the level of multimedia network management, a multimedia network teaching management system is studied and developed. The teaching information and business process of the school is analyzed, the division of the structure of the film and television multimedia information management system is completed, and the overall structure, functional structure, and database of the system are designed; Tornado technology, NoSQL database technology, jQuery technology, and Ajax technology are used to complete the development of the system. The results show that the real system can provide a highly automated platform for the school multimedia network teaching management. The system makes the teaching staff work more efficiently and accurately. The results show that the system studied has a significant effect on the multi-media teaching of minority films and television. Using the characteristics of the combination of pictures, text, sound, image, and shadow, the knowledge can be shown to students intuitively, which is helpful to relaxed and happy learning of students and stimulate their desire to learn. Multimedia teaching has become an important teaching assistant tool. This exploration can provide theoretical support for the design of network teaching information management system based on artificial intelligence, decentralize the complex network environment, and carry out decentralized management.